The behavior of concrete-encased steel composite column-beam joints under cyclic loading - Sermet, Fethi; Ercan, Emre; Hökelekli, Emin; Demir, Ali; Arisoy, Bengi; Hökelekli, Emin (Wiley, 2021)
This study outlines the cyclic loading response of a concrete-encased steel profile composite column-reinforced concrete beam connection. The experimental study performed for an interior joint. The column in joint was designed as a concrete-encased I-steel profile composite column according to Eurocode 4, and the beam was designed as a regular reinforced concrete beam according to local building codes. In order to emphasize the effect of the joint design, different steel core orientations were used. The numerical analysis was performed using ABAQUS to predict behavior of the joint. The performance of the samples compared the load-carrying capacity, ductility, and failure type. Comparisons were made using load-displacement relationships and failure mechanisms. The analysis results showed that the failure was determined by the behavior of the beam, and the joint capacity depended on the shear capacity of the beam.
Keywords: Composite Columns; Cyclic Loading; Finite Element Modeling; Reinforced Concrete Joints